GENECHOC study: genetic markers of arrhythmic risk in heart failure. (25th November 2020) - Anys, S; Rigade, S; Rigade, S; Baron, E; Baron, E; Lecointe, S; Lecointe, S; Guyomarch, B; Guyomarch, B; Klug, D; Klug, D; Babuty, D; et al.
Abstract: Background: Ventricular arrhythmic events are responsible for 50% of death in heart failure but no reliable predictive marker is known to discriminate patients at risk of fatal arrhythmia. Interestingly, familial predisposition has been reported suggesting a role of genetic factors. Purpose: Identify genetic markers increasing the arrhythmic risk in heart failure population. Method: We prospectively included heart failure patients with left ventricular ejection fraction (LVEF) under 35% and a cardioverter defibrillator in primary prevention in 22 French centres between 2009 and 2017. Patients were followed for 72 months and divided into two groups: cases with an arrhythmic event during follow-up and controls. A Genome Wide Association Study (GWAS) was done. Single Nucleotide Polymorphisms (SNPs) genotyping was performed on Affymetrix Axiom Precision Medicine Research Array plates. To complement the directly genotyped SNPs we performed large-scale imputation based on the Haplotype Reference Consortium European ancestry panel leading to a dataset of 7, 5 million of SNPs. Results: 332 cases and 567 controls were included (86% men, mean age at implantation 52±11 years). 78% of patients had ischaemic cardiopathy, 20% had dilated cardiomyopathy. Mean LVEF was 27±5%. No statistical difference was found between cases and controls on clinical parameters, biological results, electrocardiographic measures. No locus shows genome-wide significant association (p<5.10 –8 ) on the GWAS analysis. However, 16 signals with a p-value between 5.10 –8 and 5.10 –5 were investigated. eQTL and chromatin conformation point to 35 genes with cardiac expression previously associated with heart failure, cardiomyopathies, cardiogenesis, arrhythmias and inflammation. Variants identified point to regulatory regions of the genome and may then propose a molecular mechanism predisposing patients to arrhythmias. Conclusion: No locus raises genome-wide significance, but several signals with a nominal p-value point to relevant genes and pathways. Replication of the GWAS is ongoing on a cohort of 156 new patients with a less severe cardiopathy implanted with a cardioverter defibrillator in secondary prevention. Funding Acknowledgement: Type of funding source: Public hospital(s). Main funding source(s): Nantes University Hospital